A 1.1-V Low power true single-phase clock 2/3 prescaler - Tooprakai, Siraphop; Wisetphanichkij, Sompong; Tudsorn, Apirak (My University, 2017)
This paper is proposed a low-power CMOS 2/3 prescaler using true single-phase technique on 45 nm CMOS technology with 1.1 V. The true-single-phase clock divider is used to achieve low power. The prescaler is capable of operating from 1 to 16 GHz. When operating at 1 GHz, it saves more power consumption compared to that of a conventional circuit and lowpower true single-phase clock CMOS 2/3 prescalers circuit operating in divide-by-2 mode and in divide-by-3 mode, respectively.
Keywords: Divider circuit; Low power; True single phase clock circuit (TSPC)